Hormonal and HRV responses to block training guided by heart rate variability - Nikander, Aku (2017)
Aku Nikander (2017). Hormonal and HRV responses to block training guided by heart rate variability. Liikuntatieteellinen tiedekunta, Jyväskylän yliopisto, Liikuntafysiologian pro-gradu tutkielma, 67 s.